#TITLE_ALTERNATIVE# - NURJAMIL (NIM 22005006), ASEP
Weathering is a natural process of rock to reach an equilibrium condition on surface environment. In tropical region, weathering phenomena are very common processes, which are occurred when the rocks exposed to the atmosphere and hydrosphere. In addition, this process influenced by several factor, such as rock properties, climate, topography, groundwater, organic activity and aging. Studied area is located at Lembur Gunung, Cipatat and Cikamuning, Padalarang, West Bandung. The research aims are to identify the development of rock weathering grade on tufa and their impact on mineralogy, chemical and geotechnical properties. It was found that there were six rock weathering grades on tufa, i.e. the first grade (fresh rock) which is 1.2-1.5 m thick, second grade (slightly weathered) which is 1.1-1.4 m thick, third grade (medium weathered) which is 1.3-2.9 m thick, fourth grade (strongly weathered) which is 0.8-1.4 m thick, fifth grade (completely weathered) which is 1.2-2.1 m thick and the sixth grade (residual soil) which is 1.5ÃƒÂ‚Ã‚Â–2.9 m thick. There was clear relationship between weathering grade and mineral alteration. The occurrence and relative abundance of serisit, microfracture, stained and secondary mineral were significant feature and tend to increase with the increasing of weathering grade. In general, results of chemical analysis showed that there was a significant correlation between weathering grade with change of chemical composition. Composition of SiO2, MgO, K2O, CaO and Na2O tend to decrease with the increasing of weathering. While, composition of Al2O3, TiO2, and H2O- tend to increase with the increasing of weathering. Whereas, Fe2O3 tend decrease on grade I-III and to be enrichment on grade IV-VI. Nevertheless, some other indices showed poor relationships and difficult to identify. In general, the indices expressed as depletion of SiO2 and ratio oxide mobile to immobile display good correlation with the weathering grade. However, the indices base on similar geochemical behavior, such as mobile to mobile or immobile to immobile, display poor correlation with the weathering grade. Likewise, indices expressed abundance Fe2O3 display unpredictable and poor correlations with the weathering grade. Results of physical and mechanical test show that physical and mechanical properties tend to change due to weathering. Water content (w), porosity (n), void ratio (e), liquid limit (LL), plastic limit (PL), Poisson ratio (vd) and index plasticity (IP) increase with the increasing weathering grade. While, density (γ), specific gravity (Gs), Young's modulus (Ed) and shear modulus (Gd) decrease with the increasing weathering grade.